Junction gap breakdown-based fabrication of polydimethylsiloxane ionic rectifiers. (8th January 2020) - Angeli, Elena; Pezzuoli, Denise; Repetto, Diego; Guida, Patrizia; Firpo, Giuseppe; Lo Savio, Roberto; Repetto, Luca; Valbusa, Ugo
Abstract: Polymeric nanofluidic structures are good candidates for boosting the exploitation of the powerful functionalities offered by nanofluidics in many fields. The advantages offered by polymeric materials are mainly related to their low cost and ease of manufacture, compared to semiconductor industry-derived materials. When the size of functional structures is shrunk from micro to nanoscale, the limits of these materials become evident. In particular, polydimethylsiloxane (PDMS) nanostructures (nanochannels or nanoslits) experience problems of collapse during the sealing process. In this work, we propose a junction gap breakdown-based approach to fabricate polymeric nanoporous networks in situ, i.e. at the tip of an asymmetric microfunnel made of commercial PDMS. We show that these micro/nanofluidic structures have ionic current rectification characteristics, even when filled with high ionic strength solutions (1 M KCl). Moreover, analyzing the electro-kinetic transport properties of these PDMS micro/nanostructures filled with fluorescent solutions, we observed at negative bias an intra-funnel accumulation. This phenomenon results much stronger for low ionic strength solutions. As these devices combine ease of fabrication, with interesting electrical properties, they are good candidates as functional structures in many fields, spanning from biomedical applications, where they can support the development of high-sensitivity sensors, to desalination applications and ionic circuits.